Strengthening Mathematical Skills with M-Learning - Shinchiguano, Flor (2022)
The COVID-19 pandemic transformed education from face-to-face to virtual. This accelerated the creation of new learning environments based on the everyday use of mobile devices, presenting new challenges for education. Emerging technologies today drive mobile learning or m-learning. This research focuses on the development of a mobile application that seeks to strengthen the mathematical abilities of whole number empowerment in high school students in a blended mode. The application includes four missions that make up an interactive game, in which the player has three lives and accumulates points. Mate-potencia Olympics faces two players, who must meet the challenges of each mission, the winners go to a second round, until they have the winner. Students learn the process of calculating square powers, identifying each of its elements, allowing dynamic, ubiquitous and flexible learning